3D simulations of smoke exhaust system in two types of subway station platforms. Issue 1 (2nd January 2021) - Tavakolian, Zahra; Abouali, Omid; Yaghoubi, Mahmoud
Abstract: In this study, smoke evacuation in two kinds of subway station platform models, namely: an island platform station and a two side platforms station is simulated in a three-dimensional configuration. FDS 6.1.1 (Fire Dynamic Simulator) software has been employed to perform numerical simulations. The results showed noticeable effects of platform architecture on the process of smoke evacuation and emission spreading. The location of the connecting stairs (station accesses) between floors in both types of subway stations, installing the walls around these stairs in island platform type, the presence or absence of fireproof and antismoke curtains in suitable areas in two side platforms type have significant impacts on the smoke spreading. At the end, after the comparison between smoke dispersion in these two types of subway's platform, different architecture corrections were suggested and evaluated. Overall, it is concluded that an island platform station is more challenging in smoke control point of view, because the openings at the ceiling of the platform (stairway path) provide a convenient space for smoke to escape to the upper floors. In summary station architecture and even the smallest architectural changes at a subway station can change the smoke dispersion in space.